Reconstructive Effects of Percutaneous Electrical Stimulation Combined with GGT Composite on Large Bone Defect in Rats. (29th May 2013) - Yang, Bo-Yin; Huang, Tzung-Chi; Chen, Yueh-Sheng; Yao, Chun-Hsu
Abstract : Previous studies have shown the electromagnetic stimulation improves bone remodeling and bone healing. However, the effect of percutaneous electrical stimulation (ES) was not directly explored. The purpose of this study was to evaluate effect of ES on improvement of bone repair. Twenty-four adult male Sprague-Dawley rats were used for cranial implantation. We used a composite comprising genipin cross-linked gelatin mixed with tricalcium phosphate (GGT). Bone defects of all rats were filled with the GGT composites, and the rats were assigned into six groups after operation. The first three groups underwent 4, 8, and 12 weeks of ES, and the anode was connected to the backward of the defect on the neck; the cathode was connected to the front of the defect on the head. Rats were under inhalation anesthesia during the stimulation. The other three groups only received inhalation anesthesia without ES, as control groups. All the rats were examined afterward at 4, 8, and 12 weeks. Radiographic examinations including X-ray and micro-CT showed the progressive bone regeneration in the both ES and non-ES groups. The amount of the newly formed bone increased with the time between implantation and examination in the ES and non-ES groups and was higher in the ES groups. Besides, the new bone growth trended on bilateral sides in ES groups and accumulated in U-shape in non-ES groups. The results indicated that ES could improve bone repair, and the effect is higher around the cathode.